2015
DOI: 10.1515/med-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors involved in orofacial cleft predisposition – review

Abstract: Clefts that occur in children are a special topic. Avoiding risk factors, and also an early diagnosis of cleft possibility can result in minimizing or avoiding them. If on the other hand when clefts occur they require a long-term, multistage specialized treatment. Etiology of clefts seems to be related to many factors. Factors such as genetic, environmental, geographic and even race factors are important. Identification of risk factors can lead to prevention and prophylactic behaviors in order to minimize its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 90 publications
0
44
0
4
Order By: Relevance
“…Esta información solicitada tiene el propósito de recolectar la mayor cantidad de factores genéticos y/o ambientales que se pueda informar. Respecto de la etnia, en general las poblaciones amerindias y asiáticas presentan mayor frecuencia en casos de fisuras orofaciales y en menor "grado" las poblaciones caucásicas y africanas 4,5 . En un estudio de prevalencia realizado en el Hospital Félix Bulnes de Santiago 6, se encontró que el mayor porcentaje de pacientes afectados con fisura presentaban etnia amerindia, determinado por examen sanguíneo y la prevalencia del alelo O y alelo D (Rh+).…”
Section: La Ficha Clínicaunclassified
“…Esta información solicitada tiene el propósito de recolectar la mayor cantidad de factores genéticos y/o ambientales que se pueda informar. Respecto de la etnia, en general las poblaciones amerindias y asiáticas presentan mayor frecuencia en casos de fisuras orofaciales y en menor "grado" las poblaciones caucásicas y africanas 4,5 . En un estudio de prevalencia realizado en el Hospital Félix Bulnes de Santiago 6, se encontró que el mayor porcentaje de pacientes afectados con fisura presentaban etnia amerindia, determinado por examen sanguíneo y la prevalencia del alelo O y alelo D (Rh+).…”
Section: La Ficha Clínicaunclassified
“…Teratogeny and fetal abnormalities found in animal studies. Neonatal hypoadrenalism following prenatal exposure † Human observational studies have not found association with harmful effects (Bjørn et al, 2014;Fraser and Sajoo, 1995;Kawalec et al, 2015). Administration must outweigh risk to fetus ‡ Anticoagulant therapy † Drug-drug interaction: Efficacy of warfarin may be enhanced by concurrent corticosteroid therapy.…”
Section: Pending Joint Surgerymentioning
confidence: 99%
“…Several risk factors are found to cause orofacial cleft (OFC). These include geographic factors, race, family history, gender, exposure to risk factors in pregnancy, such as alcohol consumption and tobacco smoking (2,3), poor nutrition (4), viral infections, drugs and also teratogens in the workplace and home (5,6). Recent studies show that obesity during pregnancy may be related to CLP (6).…”
Section: Introductionmentioning
confidence: 99%